The Prevalence of Developmental Enamel Defects in Israeli Children and Its Association with Perinatal Conditions: A Cross-Sectional Study - Gisela Berenstein Ajzman; Nurit Dagon; Rabea Iraqi; Sigalit Blumer; Shada Fadela (MDPI AG, 2023)
Molar incisor hypomineralization (MIH) and deciduous molar hypomineralization (DMH) affect the first permanent molars and second primary molars, respectively, causing a greater dental treatment burden and worse oral health quality of life among affected children. We assessed the prevalence and risk factors of MIH and DMH among 1209 children aged 3-13 years who attended a university dental clinic in Israel in 2019-2020. Clinical examinations were conducted to assess the presence of DMH and MIH. Potential etiological factors of MIH and DMH, including demographics, the mother's perinatal health, and the child's medical history during the first three years of life, were retrieved using a questionnaire. To examine the associations between the demographic and clinical variables and the prevalence of MIH and DMH, continuous variables were tested using the Kruskal-Wallis test with Bonferroni corrections. Categorical variables were analyzed by chi-squared test. Multivariate logistic regression was conducted to evaluate which of the significant variables found in the univariate analysis could predict a diagnosis of both MIH and DMH. The prevalence of MIH and DMH was 10.3% and 6.0%, respectively. Age ≥ 5 years, taking medications during pregnancy and severe lesions were associated with a greater risk for a diagnosis of DMH + MIH. Multivariate logistic regression with adjustment for age showed that the severity of hypomineralization was positively and significantly associated with a diagnosis of MIH + DMH with an odds ratio of 4.18 (95% confidence interval 1.26-17.16), p = 0.03. MIH should be diagnosed and monitored in young children to prevent further deterioration. Moreover, a preventive and restorative program for MIH should be established.